Crypto-Christian—Post-Apophatic—Post-Secular - Drzewiecka, Ewelina (Poznańskie Studia Slawistyczne, 2022)
This article is a review of the study entitled Защото е на скрито… Християнският светоглед в творчеството на Атанас Далчев (Because It Is Hidden… The Christian Worldview in the Works of Atanas Dalchev ), byKamen Rikev ( Lublin: Wydawnictwo Uniwersytetu Marii Curie-Skłodowskiej, 2020, pp. 340 ).